A Systematic Synthetic Study of the Aqueous Chemistry of Binary Boron–Hydroxycarboxylic Acid Systems: Boron Structural Speciation Correlation to the Biotoxicity Profile. Issue 11 (23rd March 2018) - Matsia, Sevasti; Tsave, Olga; Hatzidimitriou, Antonios; Gabriel, Catherine; Bertmer, Marko; Salifoglou, Athanasios
Abstract : In an attempt to delve into the chemistry of boron, whose role in biology still remains unclear, yet its presence and influence is undisputed, research was launched into the structural speciation of B III with physiological binders. The latter molecules involve hydroxycarboxylic glycolic, 2‐hydroxy‐isobutyric, and citric acids. Their pH‐specific reactivity is systematically investigated synthetically in binary and ternary systems of B III, leading to well‐defined crystalline materials, [B(OCH2 COO)2 ](CH6 N3 ) (1 ), Na[B{OC(CH3 )2 COO}2 ] (2 ), [B(C6 H6 O7 )2 ](CH6 N3 ) (3 ), [B(C6 H6 O7 )2 ](C3 H5 N2 ) (4 ), {Na4 [B(C6 H5 O7 )(C6 H4 O7 )]} n · 2 n H2 O (5 ), and K[B(C6 H6 O7 )2 ]· 2H2 O (6 ). Complexes1 –6 are characterized physicochemically through: elemental analysis; FTIR spectroscopy; 1 H NMR, 13 C NMR, and solution 11 B NMR spectroscopy; TGA; luminescence; and X‐ray crystallography. The collective data project retention of B III tetrahedrality, with the stability of the arising complex supported by five‐membered boracyclic rings. The structurally differentiated organic ligands serve as the basis of further biological evaluation of the emerging materials in 3T3‐L1, C2C12, A549, and Saos‐2 cultures. The effect on cell survival, morphology, and migration of1, 2, and5 is investigated in a time‐, dose‐, tissue‐, and structure‐specific manner. The results portray a well‐defined biotoxic profile for soluble bioavailable binary B III –hydroxycarboxylato species, further justifying perusal of boron's structure‐specific reactivity profile in cellular physiology. Abstract : The pH‐specific reactivity in B III –hydroxycarboxylic acid systems leads to crystalline materials. Physicochemical data support B III tetrahedrality and complex stabilization through boracyclic ring formation. Exposure of four cell lines to structure‐selective binary species formulates a global biotoxicity profile, alluding to the role of boron in cellular physiology.